Anti-inflammatory effects of simvastatin during the resolution phase of experimentally formed venous thrombi. (25th April 2017) - Feng, Yaping; Lei, Bo; Zhang, Fuxian; Niu, Luyuan; Zhang, Huan; Zhang, Mingyi
Abstract : Deep venous thrombosis (DVT) is a common vascular disease and is closely linked to inflammation. Over the past decade, the potential antithrombotic effect of statins has been elucidated by clinical studies, primarily through focusing on DVT prevention. The effects of statins on DVT resolution and its underlying mechanisms have been rarely addressed. We established a rabbit model of the inferior vena cava (IVC) venous thrombosis. After 48 hours, the rabbits were treated with saline, heparin, simvastatin, or simvastatin combined with heparin, respectively, for 14 days. The migration of inflammatory cells (neutrophils, monocytes, lymphocytes) in the thrombi and injured venous wall, the plasma levels of interleukin (IL)-6, monocyte chemotactic protein 1 (MCP-1) and P-selectin, and local expression of MCP-1 and P-selectin in the venous wall were evaluated by histology, immunohistochemistry, and ELISA examinations. Our data showed that compared with saline and heparin controls, monotherapy of simvastatin and the adjunctive therapy with simvastatin and heparin significantly improved the thrombus resolution and reduced inflammatory cells migration into the venous wall, the release of the inflammatory cell adhesion molecule (P-selectin), inflammatory chemokine (MCP-1) and pleiotropic proinflammatory cytokines (IL-6) into the blood, and the local expression of P-selectin and MCP-1 in the venous wall. Simvastatin targets anti-inflammatory pathways during the resolution phase of a thrombus, providing a therapeutic potential in DVT resolution and post-thrombotic syndrome prevention.